Production of muons from heavy-flavour hadron decays at high transverse momentum in Pb-Pb collisions at √sNN=5.02 and 2.76 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Berdnikova, Anastasia; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Kroesen, Martin; López, Jorge; et al. (Physics letters, 2021)
Measurements of the production of muons from heavy-flavour hadron decays in Pb-Pb collisions at sNN=5.02 and 2.76 TeV using the ALICE detector at the LHC are reported. The nuclear modification factor RAA at sNN=5.02 TeV is measured at forward rapidity (2.5<y<4) as a function of transverse momentum pT in central, semi-central, and peripheral collisions over a wide pT interval, 3<pT<20 GeV/c, in which muons from beauty-hadron decays are expected to take over from charm as the dominant source at high pT (pT>7 GeV/c). The RAA shows an increase of the suppression of the yields of muons from heavy-flavour hadron decays with increasing centrality. A suppression by a factor of about three is observed in the 10% most central collisions. The RAA at sNN=5.02 TeV is similar to that at sNN=2.76 TeV. The precise RAA measurements have the potential to distinguish between model predictions implementing different mechanisms of parton energy loss in the high-density medium formed in heavy-ion collisions. They place important constraints for the understanding of the heavy-quark interaction with the hot and dense QCD medium.